2020
DOI: 10.1002/jsfa.10782
|View full text |Cite
|
Sign up to set email alerts
|

Using foliar nitrogen application during veraison to improve the flavor components of grape and wine

Abstract: Nitrogen is involved in the winemaking process from grapevine growth to wine fermentation, and its precise utilization in vineyards can regulate grape and wine quality. Foliar nitrogen application during veraison (FNAV) could prevent nitrogen deficiency in grape and must in nitrogen‐deficient vineyards. Moreover, FNAV also could improve certain flavor components of grape and wine, but little attention has been paid to FNAV. Therefore, this paper mainly reviews the difficulties encountered in current applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 98 publications
(314 reference statements)
1
12
0
Order By: Relevance
“…Bavaresco et al [49] also documented split applications of foliar urea during the growing season increased YAN compared to a single N application. The results of our foliar N experiments concur with many other recent studies documenting foliar N was effective in increasing diverse flavonoid contents in grapes and wines from N deficient vineyards [50][51][52][53].…”
Section: Foliar N Studies: Wine Grape Qualitysupporting
confidence: 91%
“…Bavaresco et al [49] also documented split applications of foliar urea during the growing season increased YAN compared to a single N application. The results of our foliar N experiments concur with many other recent studies documenting foliar N was effective in increasing diverse flavonoid contents in grapes and wines from N deficient vineyards [50][51][52][53].…”
Section: Foliar N Studies: Wine Grape Qualitysupporting
confidence: 91%
“…29 Garde-Cerdán et al 17 described an increase in ⊎-ionone and a decrease on (Z)-⊎-damascenone when compared with control grapes, with the lowest dose of Ur applied. Cheng et al 14 described in their work that foliar nitrogen application during veraison did not have a negative effect on volatile content in grapes. However, Garde-Cerdán et al 3 observed that MeJ foliar application produced grapes with lower ⊎-damascenone and did not affect the ⊎-ionone content, when compared with control grapes, but these effects changed with the season, since, in the other year of the study, MeJ treatment did not affect total C 13 -norisoprenoids content.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, nitrogen foliar application has been studied to improve certain grape components related with its quality, such as phenolic and volatile compounds. 14 Nitrogen is an important compound in grapes since nitrogen participates in the processes from grapevine growth to wine fermentation and its use in vineyard can improve grape and wine quality. In fact, urea (Ur) has been thoroughly studied due to its physico-chemical characteristics, owing its high water solubility and small molecular size.…”
Section: Introductionmentioning
confidence: 99%
“…This energy balance is dominated by the first Fick's Law of diffusion (Figure 1). Stomata may represent the main pathway for N absorption since they do not present a waxy layer and its waxy cuticle has different degrees of polarity resulting in an efficacious N transmission compared to leaf cuticle (Norms and Bukovac, 1968;Leece, 1976;Cheng et al, 2020). Grapevines leaves have a greater number of stomata on their abaxial side than on the adaxial one (Rogiers et al, 2011).…”
Section: Uptake Of Macro and Micro Elements By Grapevine Leavesmentioning
confidence: 99%